2022
DOI: 10.3390/gels8010038
|View full text |Cite
|
Sign up to set email alerts
|

Clozapine-Encapsulated Binary Mixed Micelles in Thermosensitive Sol–Gels for Intranasal Administration

Abstract: (1) Background: Clozapine is the most effective antipsychotic. It is, however, associated with many adverse drug reactions. Nose-to-brain (N2B) delivery offers a promising approach. This study aims to develop clozapine-encapsulated thermosensitive sol–gels for N2B delivery. (2) Methods: Poloxamer 407 and hydroxypropyl methylcellulose were mixed and hydrated with water. Glycerin and carbopol solutions were added to the mixture and stirred overnight at 2–8 °C. Clozapine 0.1% w/w was stirred with polysorbate 20 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 50 publications
(64 reference statements)
0
5
0
Order By: Relevance
“…This is in part the reasoning behind the suggested use of intranasal clozapine. 5,6 Whether the presence of PEG 400 in a liquid formulation might affect matters is a further consideration, as of course is the wider topic of the widespread use of PEG-containing laxatives. We are not aware of any studies on these topics.…”
Section: Response To Letter To the Editors From Prof D Taylormentioning
confidence: 99%
See 1 more Smart Citation
“…This is in part the reasoning behind the suggested use of intranasal clozapine. 5,6 Whether the presence of PEG 400 in a liquid formulation might affect matters is a further consideration, as of course is the wider topic of the widespread use of PEG-containing laxatives. We are not aware of any studies on these topics.…”
Section: Response To Letter To the Editors From Prof D Taylormentioning
confidence: 99%
“…However, this would be expected to give improved bioavailability if anything because the first-pass effect would be bypassed. This is in part the reasoning behind the suggested use of intranasal clozapine 5,6 . Whether the presence of PEG 400 in a liquid formulation might affect matters is a further consideration, as of course is the wider topic of the widespread use of PEG-containing laxatives.…”
mentioning
confidence: 99%
“…11 Recently many nasal CLZ nano preparations have been developed; nanosized binary mixed micelles intranasal gel was developed using poloxamer/polysorbate which improved both drug permeation rate through nasal sheep mucosa and system stability. 12 Patel et al formulated CLZ nanosuspension for nose to brain delivery which demonstrated higher CLZ concentration and faster absorption in the brain compared with CLZ suspension. 13 Another approach for intranasal CLZ appeared in the formulation of polymeric nanomixed micelles using Tetronic® 904/Synperonic® PE/F127, the optimized formula was radiolabeled by 99m Tc to ensure the direct delivery of CLZ from nose to brain and high bioavailability of the drug in the central nervous system (CNS).…”
Section: Introductionmentioning
confidence: 99%
“…Local delivery of therapeutic agents through hydrogels can provide more sustained release and high doses of medicinal drugs directly at the site of tumor tissue, reducing dosing frequency, preventing prolonged blood circulation, reducing side effects on normal tissue, and improving therapeutic outcomes of patients. Poloxamer hydrogel is a classical thermo-sensitive hydrogel system that has enabled the injectable [ 18 ], transdermal [ 19 ], mucosal adhesion [ 20 ], nasal [ 21 ], and ophthalmic [ 22 ] delivery of a variety of drugs such as curcumin [ 23 ], quercetin [ 24 ], resveratrol [ 25 ], and tannic acid [ 26 ]. Thermo-sensitive hydrogels remain liquid at room temperature to improve their injectability and diffusivity.…”
Section: Introductionmentioning
confidence: 99%